The English Works of Thomas Hobbes. Electronic edition. Leviathan - Hobbes, Thomas, 1588-1679 (InteLex Corporation, 1995)
The Past Masters The English Works of Thomas Hobbes database contains all of Hobbes' English Works as published in The English Works of Thomas Hobbes, London: J Bohn, 1839-1845. This volume is Leviathan.
Note: De cive and Leviathan are based on the 1651 edition, with variants to the Molesworth edition noted. The Elements of Law is a reproduction of the Ferdinand Tönnies edition.
Keywords: Philosophy.; Philosophy -- Early works to 1800.; Philosophy -- Law.; Political science -- Philosophy.; Knowledge, Theory of.